Faktor-Faktor Yang Mempengaruhi Perilaku PenggunaanAntibiotik Tanpa Resep Pada Mahasiswa/I Universitas HKBP Nommensen Medan - Henny Erina Saurmauli Ompusunggu (Nommensen Journal of Medicine, 2020)
Background : Antibiotics are drugs that work to prevent and treat infection caused by bacteria. However, improper use of antibiotics can cause antibiotic resistance. Antibiotic resistance occurs due to irrational used without a prescription. The aim of this study is to determine the predisposition factors of non prescription use of antibiotics in Universitas HKBP Nommensen students. Methods: This research is descriptive study. Sample of this study were 210 active students of Universitas HKBP Nommensen, who were selected by using purposive sampling technique. The predisposition factors of non prescription use of antibiotics obtained from quetionnaire. Results: The predisposition factors of non prescription use of antibiotics in Universitas HKBP Nommensen students were poor knowledge of antibiotics, the suggestion of relatives or neighbors and the experience of consuming antibiotics to cure the same disease before. Financial problem was not a dominant factor. Conclusion: Poor knowledge of antibiotics, the suggestion of relatives or neighbors and the experience of consuming antibiotics before are the dominant predisposition factors of non prescription use of antibiotics.